(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The intention of the research is investigating the effects of English short stories in the process of teaching the foreign language. The Short stories method cannot be ideal and unique for all kinds of learners since what can seem appropriate for one student can be discouraging for another. Perhaps the best way to develop speaking activities appropriately and productively is to explore students’ feelings and beliefs about the language. The research includes a literature review where the researches on speaking teaching methods and ways are discussed.